2016
DOI: 10.1176/appi.ajp.2016.15081035
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Antidepressants Added to Antipsychotics for Schizophrenia: A Systematic Review and Meta-Analysis

Abstract: Analysis of primary outcomes (depressive and negative symptoms) suggests small, beneficial effects of adjunctive antidepressants. It would appear that this augmentation can be accomplished with a low risk of exacerbation of psychosis and adverse effects. However, secondary and subgroup analyses should be interpreted cautiously and considered exploratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
128
5
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(147 citation statements)
references
References 64 publications
9
128
5
5
Order By: Relevance
“…On the other hand, depressive symptoms correlated with negative symptoms and general adverse events. This may be supported by a recent study on schizophrenia patients, which showed a beneficial effect of adjunctive antidepressants on depressive and negative symptoms (Helfer et al 2015), with a relatively low risk of exacerbation of psychosis and adverse effects (Helfer et al 2015;Mosheva et al 2016).…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, depressive symptoms correlated with negative symptoms and general adverse events. This may be supported by a recent study on schizophrenia patients, which showed a beneficial effect of adjunctive antidepressants on depressive and negative symptoms (Helfer et al 2015), with a relatively low risk of exacerbation of psychosis and adverse effects (Helfer et al 2015;Mosheva et al 2016).…”
Section: Discussionmentioning
confidence: 70%
“…ADs were often prescribed for negative and depressive symptoms and cognitive impairment in schizophrenia . Negative and depressive symptoms could be improved in around a third of schizophrenia patients receiving ADs and adjunctive ADs . This may be related to the effect of ADs in modifying serotonergic (5‐HT) dysfunction that is thought to be involved in the pathophysiology of psychotic symptoms …”
Section: Discussionmentioning
confidence: 99%
“…Despite their frequent use on a pragmatic basis, there have been few sufficiently powered, randomized controlled trials of antidepressants for the treatment of depression in schizophrenia, although recent meta-analysis gives some limited evidence of effect. 44 Cognitive behavioral therapy for psychosis (CBTp) has been the subject of much research in recent years, however has primarily focused on effectiveness for positive symptoms, transition from high-risk status and more recently on distress. No CBTp studies have used depression as a primary outcome or target of therapy.…”
Section: Treatment Of Depressionmentioning
confidence: 99%